Treatment Refusal and Family Accommodation - Gordon, William M. (Pragmatic Case Studies in Psychotherapy, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This commentary discusses a case study by James Marinchak (2013), who treated a mother’s accommodation of her adult son’s obsessive-compulsive disorder (OCD). A variety of issues raised by the case are considered. These include: the relationship between dependency and OCD, the presence of rituals without apparent obsessions, the pros and cons of treating one primary relative versus the family, ways of handling treatment refusal, methodological issues, and the relationship between stress, high emotionality and severity of OCD. The main topic of helping families cope with OCD when the person manifesting it refuses treatment is an overlooked and important area of research.